IDENTIFICATION OF CRITICAL SUCCESS FACTORS FOR THE MANAGEMENT OF CONSTRUCTION WASTE: IDENTIFICATION OF CRITICAL SUCCESS FACTORS FOR THE MANAGEMENT OF CONSTRUCTION WASTE - Silva, Wesley; da Silva, Adalberon Brenno Quirino; Galindo, Anna Beatriz Monteiro Garcia; Cardoso, Sérgio Diego Serafim; Silva, Emerson; de Moraes, Wanny (Brazilian Journal of Production Engineering, 2020)
The generation of construction waste is a problem that has negative environmental, economic and social impacts. In this sense, it is important that these residues are well managed in order to mitigate the impacts caused. Therefore, it is necessary to understand the main factors that are critical for the management of this waste. Thus, the objective of the present study was to identify the main critical success factors (CSF) for the management of construction waste in the city of Caruaru-PE, which was the city object of this study. In order to meet this objective, a literature review was carried out to survey the main CSF presented and hypotheses were formulated about them. Therefore, a questionnaire was applied to students and professionals in the field of civil construction to assess their perception of the CSF raised in the literature. Of the eleven CSF surveyed, the data collected showed evidence that only nine of them were verified in practice. This study also allowed the construction companies to develop action plans to properly manage this waste, the government to monitor the activities developed more closely and the population to demand improvements in management.